Model Pembelajaran Creative Problem Solving (CPS) dalam Meningkatkan Kemampuan Berpikir Kreatif dalam Pembelajaran Matematika - Aprilia, Sabila; Luthfiatuzzahro, Hani; Kusumawati, Annisa Cahya; Adeliana, Dina (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The aim of the literature study is to find out whether the Creative Problem Solving (CPS) Model can improve students' creative thinking abilities in mathematics classes. Literature study research methodology. The analysis method is descriptive analysis by analyzing by providing a clear understanding and explanation. Based on the results of the literature analysis of the three journals, it was found that the Creative Problem Solving learning model was effective in improving students' creative thinking abilities during the mathematics learning process. Based on this, teachers can use this model to improve students' creative thinking abilities during the mathematics learning process.